THE USE OF PLANT BIOTECHNOLOGY IN THE PRODUCTION OF BIOLOGICALLY ACTIVE NATURAL COMPOUNDS (REMUNOM, 2023)
Historically, natural products represent an important source of substances used in the development of new therapies. The medicinal activities present in plants are mainly due to the synthesis of substances resulting from their secondary metabolism. These metabolic pathways can be activated by interactions between plants and the environment, including nutritional stresses. In addition to environmental influences, the composition of substances may vary according to the plant tissue, the stage of development in which it presents itself and the genetic character of the individuals used. The use of plants as raw materials for the large-scale production of medicines is linked to some problems, such as low concentrations of metabolites produced under natural conditions, low capacity for chemical standardization and genetic erosion resulting from predatory extractivism. As a biotechnological tool, plant tissue culture offers useful techniques for research aimed at improving the production and final obtaining of secondary metabolites; both by the mass propagation of the plant material used and production of secondary metabolites in vitro, as well as by the selection and conservation of germplasm of interest. In the present study, a brief review of the main biotechnological techniques employed in the cultivation and propagation of plant species of medicinal and economic interest was made.